LANGUAGE, GENDER, AND SYMBOLIC POWER IN THE DIDONG DOAH TRADITION: AN ANTHROPOLINGUISTIC ANALYSIS OF WOMEN'S ROLES IN KARO CULTURE - Alemina Parangin-angin (Journal of Oral Traditions, 2025)
This study aims to explore the dynamics of symbolic power and gender relations within the Karo oral tradition through the lens of Didong Doah songs, focusing particularly on the performative roles of women as conveyors of moral and cultural messages. Employing an anthropolinguistic approach, the research examines how language in Didong Doah serves as a medium for cultural expression that reflects symbolic domination, gender identity construction, and social relational patterns. The study was conducted in Kuta Buluh Village, Karo Regency, utilizing qualitative methods that integrate participant observation, in-depth interviews, and audio-visual documentation. Findings reveal that women are not merely cultural inheritors but active agents in social transformation, utilizing symbolic language as a tool of narrative power. This study contributes significantly to the development of gender performativity theory, cultural sociolinguistics, and the revitalization of local traditions within the framework of women's empowerment